2019
DOI: 10.1186/s12887-019-1559-7
|View full text |Cite
|
Sign up to set email alerts
|

The associations between injury mechanism and extended hospital stay among pediatric patients: findings from a trauma Center in Saudi Arabia

Abstract: Background A hospitalized patient’s length of stay (LOS) can have a significant impact on the performance and operating costs of a healthcare facility. Among pediatric patients, traumatic injuries are common causes of emergency room visits and hospitalizations. In Saudi Arabia, little is known about the burden of pediatric traumas on population health and the healthcare facilities. Therefore, the aim of this study was to investigate the associations between traumatic pediatric injury mechanisms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…Males formed about 60.7% of the pediatric patients in the current study which comes in accordance with much of the literature (12)(13)(14)(15) . The overrepresentation of males among trauma patients perhaps because boys are more inclined to play in hazardous environments without adult supervision.…”
Section: Discussionsupporting
confidence: 91%
“…Males formed about 60.7% of the pediatric patients in the current study which comes in accordance with much of the literature (12)(13)(14)(15) . The overrepresentation of males among trauma patients perhaps because boys are more inclined to play in hazardous environments without adult supervision.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, blunt injuries caused by falls and MVC were the leading cause of deaths in overall injuries [ 21 ]. Additionally, MVC was reported to be the primary cause of injury that led to an extended length of stay [ 22 ]. In fact, the mechanism of injury was found to be a significant predictor of extended length of stay with higher odds for MVC and burns (OR: 16.2, OR: 14.5, respectively, P < 0.001) as opposed to falls [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The leading cause of deaths among patients was blunt injury (92%). The mortality rate was 2.8% Riyadh 16 (Alghnam et al, 2019) [ 22 ] 2001 - 2018 Retrospective N=5563 Males represented 75.8% of admitted children following injuries. The most common type of injury was fall (31.5%), followed by an MVC (28.5%) The prevalence of children who had extended length of stay was 14%.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were published between 1975 [29] and 2021 [30][31][32]. Studies most commonly reported data on drowning from Iran (27 studies ), Saudia Arabia (11 studies [31,32,[60][61][62][63][64][65][66][67][68]) and Pakistan (10 studies [69][70][71][72][73][74][75][76][77][78]). There were 3 studies which reported on multiple countries within the EMR [79][80][81] and 3 studies which reported on the EMR as a whole [3,82,83] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%